INTEGRATED VIEW OF FINANCIAL, SOCIAL AND ETHICAL INFORMATION - Choy Zevallos, Elsa Esther (2009)
At present, the traditional accounting information, which expresses the economic and financial results of an entity, does not meet the needs of knowledge about the overall organizational performance that have shareholders, customers, investors, government, civil society organizations and other stakeholders of the company The need for information that includes a vision, in the social, economic, political, environmental, educational and its a vitally important aspect to this business and it is the accountant, which is responsible for processing economic and financial information, together with social and environmental aspects. The purpose of this subject is to present a new approach to financial reporting, which reflects the influence of environment on the development of activities, with social responsibility of the economic unit. Also highlight the critical involvement of the profession and the role of ethics in this activity.